Application of GIS and remote sensing in detecting coastal reclamation in the coastal areas of Hai Phong - Ha Long from 1990 to 2020 - Do , Thi Thu Huong; Tran, Dinh Lan; Nguyen, Thi Thu Ha; Nguyen, Dac Ve; Nguyen, Van Thao (Vietnam Journal of Marine Science and Technology, 2025)
Coastal reclamation transforms coastal areas into usable land for urban, agricultural, and industrial purposes. This study evaluates the status of coastal reclamation from 1990 to 2020 in the Hai Phong - Ha Long coastal area using high and medium-resolution satellite images and GIS techniques. The findings revealed a significant increase in reclamation activity, with 900 hectares reclaimed in 1990–2000, 3,161 hectares in 2000–2010, and 3,434 hectares in 2010–2020. Over different periods, the objectives of reclamation activities shifted. In 1990-2000 and 2000–2010, the focus was primarily on facilitating aquaculture and mangrove cultivation. However, from 2010 onwards, the focus shifted to the developing industrial parks, urban areas, and recreational spaces. Coastal reclamation activities have led to changes in the coastline’s characteristics, including length and shape alterations. Over 30 years, the total coastline length has increased by 58.4 km, with the proportion of artificial coastlines increasing by 33.5%. Additionally, coastal reclamation has converted significant areas of mangrove forests, tidal flats, and shallow coastal waters into new land. Therefore, strong policies and integrated coastal zone management are needed to ensure sustainable development and preserve coastal ecosystems.